Supply and Demand, Allocation and Wage Inequality: An International Comparison - Arnaud Dupuy; Lex Borghans (Institute for the Study of Labor (IZA), 2003)
In this paper, we develop an allocation model of workers differentiated by their field of study to test whether international differences in the wage structure can be explained by differences in labor demand and supply in each country. The model explicitly takes into account the effects of supply and demand shifts on the allocation structure to disentangle country specific differences in the recruitment for one occupation from real supply-demand effects. Empirical results based on data for nine countries show that cross-country differences in wage inequality explain at least 2/3 of the differences in labor demand and supply.
Keywords: J23; J21; J31; 330; allocation; wage inequality; Lohnstruktur; Arbeitsangebot; Arbeitsnachfrage; Allokation; Schätzung; Welt